(untitled) (Conferencea, 2023)
The article analyzes the problem of the formation of ecological competence of future specialists of preschool educational institutions. Determine the environmental competence of the future experts of Dow as an important personal quality constituting their professional competence, determined by a combination of environmental knowledge, perceptions, attitudes, beliefs, ideals, moral student evaluations concerning the environment, nature in general, which are integrated into the personal system of ecological values of the future expert of preschool educational institution.